2016
DOI: 10.1016/j.stem.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

3D Chromosome Regulatory Landscape of Human Pluripotent Cells

Abstract: SUMMARY In this study, we describe the 3D regulatory chromosome structural landscape of human naive and primed embryonic stem cells. To devise this map, we identified transcriptional enhancers and insulators in these cells and placed them within the context of cohesin-associated CTCF-CTCF loops using cohesin ChIA-PET data. The CTCF-CTCF loops we identified form a chromosomal framework of insulated neighborhoods, which in turn form topologically associated domains (TADs), that are largely preserved during trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
435
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(468 citation statements)
references
References 75 publications
(128 reference statements)
32
435
0
1
Order By: Relevance
“…These analyses suggest that active enhancer elements are bound by transcription factors and loop over long distances to contact target genes to regulate transcription. An emerging model suggests promoter-enhancer interactions typically only occur within megabase-sized topological-associated domains (TAD; Dixon et al 2012;Nora et al 2012), as defined by high DNA interaction frequency based on genome-wide chromosome capture data or within such TADs in insulated neighborhoods restricted by cohesin-associated CTCF-CTCF loops (Handoko et al 2011;DeMare et al 2013;Dowen et al 2014;Rao et al 2014;Ji et al 2016). Notably, there is mounting evidence that changes in 3D structure, potentially through sequence-specific disruption of CTCF interaction, might contribute to disease development (Ji et al 2016).…”
Section: Epigenomic Signatures To Prioritize Gwas-identified Risk Varmentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses suggest that active enhancer elements are bound by transcription factors and loop over long distances to contact target genes to regulate transcription. An emerging model suggests promoter-enhancer interactions typically only occur within megabase-sized topological-associated domains (TAD; Dixon et al 2012;Nora et al 2012), as defined by high DNA interaction frequency based on genome-wide chromosome capture data or within such TADs in insulated neighborhoods restricted by cohesin-associated CTCF-CTCF loops (Handoko et al 2011;DeMare et al 2013;Dowen et al 2014;Rao et al 2014;Ji et al 2016). Notably, there is mounting evidence that changes in 3D structure, potentially through sequence-specific disruption of CTCF interaction, might contribute to disease development (Ji et al 2016).…”
Section: Epigenomic Signatures To Prioritize Gwas-identified Risk Varmentioning
confidence: 99%
“…An emerging model suggests promoter-enhancer interactions typically only occur within megabase-sized topological-associated domains (TAD; Dixon et al 2012;Nora et al 2012), as defined by high DNA interaction frequency based on genome-wide chromosome capture data or within such TADs in insulated neighborhoods restricted by cohesin-associated CTCF-CTCF loops (Handoko et al 2011;DeMare et al 2013;Dowen et al 2014;Rao et al 2014;Ji et al 2016). Notably, there is mounting evidence that changes in 3D structure, potentially through sequence-specific disruption of CTCF interaction, might contribute to disease development (Ji et al 2016). Integrating datasets of cell type-specific changes in enhancer-promoter interactions and information about the 3D structure of the genome will further help us to assign disease-associated risk variants in enhancer sequences to target genes and provide supporting evidence to identify functional disease-associated risk variants and deregulated target genes.…”
Section: Epigenomic Signatures To Prioritize Gwas-identified Risk Varmentioning
confidence: 99%
“…TADs partition chromosomes into blocks of DNA at scales of hundreds of kilobases to megabases of DNA and are frequently bounded at inverted CTCF-binding sites, suggesting that CTCF-mediated loops comprise a major organizing principle for the genome (Cook and Gove 1992;Dekker and Heard 2015;Dekker and Misteli 2015;Dixon et al 2012;Guo et al 2015;Ji et al 2016;Pope et al 2014;Smith et al 2016;Tang et al 2015;Valton and Dekker 2016). CTCF and cohesin are enriched at TAD boundaries (Guo et al 2015;Ji et al 2016;Katainen et al 2015;Rao et al 2015;Sofueva et al 2013;Tang et al 2015;Xiao et al 2011;Zuin et al 2014).…”
Section: Intranuclear Topology Topography and Cartographymentioning
confidence: 99%
“…The insulation of TADs is mediated by chromosome-structuring proteins, such as CTCF (15,16). Global analysis of binding factor sequence showed that CTCF sites are among the sequences most frequently altered in human cancer and that these mutations occur frequently near cancer-associated genes (17). Abe Weintraub (from Richard Young's laboratory, MIT, USA) presented recent examples from T-cell acute lymphoblastic leukemia (T-ALL) in which recurrent microdeletions occurred at the boundary sites of insulated neighboring proto-oncogenes, which can drive cellular transformation (18).…”
Section: Cancermentioning
confidence: 99%